KEKUATAN KEABSAHAN ALAT BUKTI ELEKTRONIK DALAM PENYELESAIAN PERKARA PIDANA DI INDONESIA - Sari, Indah (Universitas Dirgantara Marsekal Suryadarma, 2024)
The background of this study is about the development of information technology, which has brought a big development in people’s lives, and more importantly, about solving criminal cases in Indonesia. In criminal procedural law, legitimate proof is needed, as it is regulated in Chapter 184, paragraph 1,of the Code of Criminal Procedure (KUHAP) about witness evidence, expert evidence, the presence of a clue, the defendant’s letter, and its evidence. What if that evidence is in the form of something electronic, also known as electronic evidence? Can this proof be used as legitimate evidence in solving criminal cases in Indonesia? This provision is already arranged in the Electronic Information and Transactions Law (UU ITE). The questions that need to be answered in this article are: first, what forms of electronic evidence are beneficial for solving criminal cases in Indonesia? Second, how to confirm the validity of the proof of using electronic evidence is for solving criminal cases in Indonesia? The kind of typing that the writer uses in this research is descriptive research (describing an object and taking simple conclusion from it) with secondary data and use statute approach, case approach, and conceptual approach. This kind of technique is collected by library research and the data will be analyzed qualitatively. The purpose of this writing are to study and analyze what forms of electronic evidence are beneficial for solving criminal cases in Indonesia and to know how strong the validity of electronic evidence is for solving criminal cases in Indonesia.